Evidence for a 12 kDa “Carrier Protein” for Natriuretic Hormone - Gonick, Harvey C. (Frontiers in Endocrinology, 2014)
The search for the elusive natriuretic hormone continues. In this review evidence is presented that isolating the carrier protein for natriuretic hormone is a necessary first step before splitting off the final hormone. The carrier protein has a molecular weight of 12 kDa while the final hormone has a molecular weight of 408 daltons. Both compounds inhibit Na-K-ATPase but the compound containing the carrier protein predominates. The question has been raised as to whether the carrier protein is in actuality proANF, a 17 kDa protein that can be split between a 14 kDa protein (the presumptive proANF) and the 3 kDa ANF.